2023
DOI: 10.1098/rstb.2022.0156
|View full text |Cite
|
Sign up to set email alerts
|

Why do some bird species incorporate more anthropogenic materials into their nests than others?

Abstract: Many bird species incorporate anthropogenic materials (e.g. sweet wrappers, cigarette butts and plastic strings) into their nests. Anthropogenic materials have become widely available as nesting materials in marine and terrestrial environments globally. These human-made objects can provide important benefits to birds such as serving as reliable signals to conspecifics or protecting against ectoparasites, but they can also incur fundamental survival and energetic costs via offspring entanglement and reduced ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 96 publications
(280 reference statements)
0
12
0
Order By: Relevance
“…The materials used to construct a nest can reflect various physical and mechanical properties, including those known or thought to contribute to offspring survival (Bailey et al, 2014;Bailey et al, 2016;Biddle et al, 2018;Breen et al, 2021;Hilton et al, 2004). We here (Jagiello et al, 2023;Sheard, Stott, et al, 2023). We present information on nest materials for 7020 species (8192 entries); for one potential categorization of these materials, see .…”
Section: Nest Materialsmentioning
confidence: 99%
“…The materials used to construct a nest can reflect various physical and mechanical properties, including those known or thought to contribute to offspring survival (Bailey et al, 2014;Bailey et al, 2016;Biddle et al, 2018;Breen et al, 2021;Hilton et al, 2004). We here (Jagiello et al, 2023;Sheard, Stott, et al, 2023). We present information on nest materials for 7020 species (8192 entries); for one potential categorization of these materials, see .…”
Section: Nest Materialsmentioning
confidence: 99%
“…Jagiello et al . [ 76 ] use the outputs of a systematic literature search to compile a database regarding the occurrence of anthropogenic nest materials in birds' nests worldwide and employ phylogenetically controlled interspecific analyses to examine the main drivers of the presence of anthropogenic nest material in nests. The type of nest and the degree of sexual dimorphism between pairs of birds significantly influence the use of anthropogenic materials by birds, although the pattern of anthropogenic material use does not exhibit a phylogenetic signal, which suggests that the inclusion of such materials into nests is widespread in the world's bird species.…”
Section: Nests In the Anthropocenementioning
confidence: 99%
“…The type of nest and the degree of sexual dimorphism between pairs of birds significantly influence the use of anthropogenic materials by birds, although the pattern of anthropogenic material use does not exhibit a phylogenetic signal, which suggests that the inclusion of such materials into nests is widespread in the world's bird species. This study thus acts as a comparative guide as to which species likely incorporate human-made components into their nests [ 76 ].…”
Section: Nests In the Anthropocenementioning
confidence: 99%
“…pressures (Deeming & Reynolds, 2016;Mainwaring & Hartley, 2013;Reid et al, 2000), and the materials used to construct a nest can reflect various physical and mechanical properties known or thought to contribute to offspring survival (Bailey et al, 2014(Bailey et al, , 2016Breen et al, 2021). Some bird species are known to incorporate anthropogenic (human-made) materials into their nests (reviewed in Jagiello et al, 2019Jagiello et al, , 2023Reynolds et al, 2019). This phenomenon has ranged from a 1933 record of a pied crow (known then as Corvus scapulatus, now Corvus albus) placing various wire pieces into a 20-lb nest (Warren, 1933) to reports of plastic debris in 12% of nests in 14 northwest European seabird species (O'Hanlon et al, 2021) and in up to 100% of yellow-legged gull (Larus michahellis) nests in Barcelona (Galimany et al, 2023).…”
mentioning
confidence: 99%
“…A recent study of anthropogenic nest material use in 125 species of birds (Jagiello et al, 2023) identified two potential correlates of interspecific variation in the extent of this phenomenon: dome nesting and sexual body mass dimorphism, with birds that build domes and/or have generally larger males than females less likely to incorporate anthropogenic material. They found no evidence within this sample that anthropogenic nest material correlated with any other nesting variable (type, habitat, component), life-history trait (longevity, fecundity, developmental mode), range size, bill size, brain size, proximity to human landscape modification, mating system or sex of the nest builder; moreover, several models (on different sample sizes and with different combinations of predictor variables) indicated that the correlations with dome nesting and/or sexual dimorphism were in fact not statistically significant.…”
mentioning
confidence: 99%